2005
DOI: 10.1097/01.ta.0000169867.08607.f1
|View full text |Cite
|
Sign up to set email alerts
|

Escharotomy Using an Enzymatic Debridement Agent for Treating Experimental Burn-Induced Compartment Syndrome in an Animal Model

Abstract: Escharectomy using an effective enzymatic debriding agent is potentially an adequate, simple, fast and effective procedure to treat BICS, it has the added benefit of burn debridement without surgical escharotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…It is a fast-acting, reliable and complication-free enzymatic debriding agent that is capable of lysing the burn eschar within 4 h. Interestingly, bromelain removes necrotic tissue without damaging the normally healing underlying wound [6][7][8][9]. A pilot study showed that collagenase and polymyxin B sulfate may have a superior effect when compared to silver sulfadiazine alone [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is a fast-acting, reliable and complication-free enzymatic debriding agent that is capable of lysing the burn eschar within 4 h. Interestingly, bromelain removes necrotic tissue without damaging the normally healing underlying wound [6][7][8][9]. A pilot study showed that collagenase and polymyxin B sulfate may have a superior effect when compared to silver sulfadiazine alone [10].…”
Section: Discussionmentioning
confidence: 99%
“…Bromelain has been extensively used in burn debridement [70][71][72]. Therefore, the enzyme could be a tenable option for surgical escharotomy in deep burn patients.…”
Section: Burn Debridement and Wound Healingmentioning
confidence: 99%
“…The enzyme affected only burned skin and resulted in minimal blood loss [73]. In a porcine model of burn-induced compartment syndrome, circumferential limb burns treated with bromelain exhibited a significant reduction in intra-compartmental pressures [71]. In addition, Rosenberg an co-workers [70] reported complete scar debridement (burned and traumatized tissue) after one to two brief bromelain applications with minimal side effects and no blood loss.…”
Section: Burn Debridement and Wound Healingmentioning
confidence: 99%
“…Currently available non‐surgical debridement agents, either enzymatic (eg, collagenase) or autolytic (eg, medicinal honey), are slow‐acting, and there is little evidence to suggest that the use of any currently available debridement agent for chronic wounds is beneficial for wound healing when compared with traditional (saline soaking) or other control treatments. Bromelain‐based debridement (BBD), performed with a concentrate of proteolytic enzymes enriched in bromelain (MediWound Ltd, Yavne, Israel), has been proven to be a rapid, efficient, and safe enzymatic debridement agent in burns, with the additional benefit of selectivity, that is, removal of non‐viable tissue and preservation of viable tissue . In light of the unmet need for a rapid and effective non‐surgical debridement agent for chronic wounds and these positive results using BBD for burn eschar removal, 2 similar consecutive concept validation studies were conducted to provide a first impression of the safety and efficacy of BBD in chronic wounds.…”
Section: Introductionmentioning
confidence: 99%